2022
DOI: 10.3389/fchem.2022.1062352
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of compounds targeting SARS-CoV-2 helicase

Abstract: The economical and societal impact of COVID-19 has made the development of vaccines and drugs to combat SARS-CoV-2 infection a priority. While the SARS-CoV-2 spike protein has been widely explored as a drug target, the SARS-CoV-2 helicase (nsp13) does not have any approved medication. The helicase shares 99.8% similarity with its SARS-CoV-1 homolog and was shown to be essential for viral replication. This review summarizes and builds on existing research on inhibitors of SARS-CoV-1 and SARS-CoV-2 helicases. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 111 publications
0
3
0
Order By: Relevance
“… 23 The published SARS-CoV Nsp13 helicase activity inhibitor, SSYA10-001, also inhibited SARS-CoV-2 Nsp13 ( Figure 2 D), which further validated the experimental setup. 17 , 31 33 IOWH-032 and TEL were titrated into duplex-DNA reactions initiated with excess ATP with and without detergent to assess the possible effects of compound aggregation ( Figures 2 E,F and Figures S5C,D ). Both compounds disrupted Nsp13 helicase activity at micromolar concentrations regardless of the presence of detergent, which indicated that inhibition resulted from each compound binding to enzyme, and not aggregate formation.…”
Section: Resultsmentioning
confidence: 99%
“… 23 The published SARS-CoV Nsp13 helicase activity inhibitor, SSYA10-001, also inhibited SARS-CoV-2 Nsp13 ( Figure 2 D), which further validated the experimental setup. 17 , 31 33 IOWH-032 and TEL were titrated into duplex-DNA reactions initiated with excess ATP with and without detergent to assess the possible effects of compound aggregation ( Figures 2 E,F and Figures S5C,D ). Both compounds disrupted Nsp13 helicase activity at micromolar concentrations regardless of the presence of detergent, which indicated that inhibition resulted from each compound binding to enzyme, and not aggregate formation.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds reported in non-English publications could be skipped in this review. In a recently published review paper, 111 some of the cited references reported a few compounds tested against the SARS-CoV-2 helicase; however, these studies did not appear in our list of articles . This could be attributed to the fact that their titles and abstracts did not fit the inclusion criteria of this current systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 helicase is a 5′→3′ translocated helicase, which is powered by deoxyribonucleotide triphosphate. It acts on deoxyribonucleic acid substrates, catalyzes the unwinding of double-stranded RNA and then replicates in large quantities, playing a key role in viral genome replication [ 86 , 87 , 88 ].…”
Section: Fluorescence-based Drug Screening Methods For Novel Coronavi...mentioning
confidence: 99%